Lead uptake and translocation pathways in soybean seedlings: the role of ion competition and transpiration rates - Blanco, Andrés; Pignata, María L.; Lascano, Hernan Ramiro; Salazar, María J.; Rodriguez, Judith Hebelen (Springer, 2021)
Glycine max (L.) Merr. (soybean) crop plants have been found to have high lead (Pb) levels in aerial organs; however, knowledge about the processes involved in the incorporation, and subsequent translocation and accumulation of the metal in the plants is scarce. Considering the toxicity of this heavy metal, the aim of the present study was to evaluate Pb uptake and translocation, and their toxic effects on soybean seedlings via experiments of ionic competition with Ca2+ (2.5 mM, Ca:Pb 1:1) and alteration of the transpiration flow [0.25 mM Pb(NO3)2]. The following variables were analyzed: biomass, leaf area (morphological parameters), photosynthetic efficiency, biochemical response (considered physiological stress markers: antioxidant power, chlorophylls, carotenoids, starch, proteins, sugars, and malondialdehyde), and Pb content. Results showed that soybean seedlings can accumulate high Pb concentration in its organs; however, in general, no morpho-physiological Pb stress symptoms were observed, except for lipid peroxidation and antioxidant power. The treatment with Ca ions was not effective in reducing Pb entry into root over time when both Ca and Pb where present in the grow solution. Alteration of the transpiration rate in soybean showed that the air flow increased the consumption of solutions, regardless of the treatments.